Multiple transcriptome comparisons reveal the essential roles of FLOWERING LOCUS T in floral initiation and SOC1 and SVP in floral activation in blueberry - Song, Guo-qing; Carter, Benjamin B.; Zhong, Gan-Yuan (Frontiers in Genetics, 2023)
The flowering mechanisms, especially chilling requirement-regulated flowering, in deciduous woody crops remain to be elucidated. Flower buds of northern highbush blueberry cultivar Aurora require approximately 1,000 chilling hours to bloom. Overexpression of a blueberry FLOWERING LOCUS T (VcFT) enabled precocious flowering of transgenic ‘Aurora’ mainly in non-terminated apical shoots during flower bud formation, meanwhile, most of the mature flower buds could not break until they received enough chilling hours. In this study, we identified two groups of differentially expressed genes (DEGs) in flower buds caused by VcFT overexpression (VcFT-OX) and full chilling. We compared the two groups of DEGs with a focus on flowering pathway genes. We found: 1) In nonchilled flower buds, VcFT-OX drove a high VcFT expression and repressed expression of a major MADS-box gene, blueberry SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 (VcSOC1) resulting an increased VcFT/VcSOC1 expression ratio; 2) In fully chilled flower buds that are ready to break, the chilling upregulated VcSOC1 expression in nontransgenic ‘Aurora’ and repressed VcFT expression in VcFT-OX ‘Aurora’, and each resulted in a decreased ratio of VcFT to VcSOC1; additionally, expression of a blueberry SHORT VEGETATIVE PHASE (SVP) was upregulated in chilled flower buds of both transgenic and nontransgenic’ Aurora’. Together with additional analysis of VcFT and VcSOC1 in the transcriptome data of other genotypes and tissues, we provide evidence to support that VcFT expression plays a significant role in promoting floral initiation and that VcSOC1 expression is a key floral activator. We thus propose a new hypothesis on blueberry flowering mechanism, of which the ratios of VcFT-to-VcSOC1 at transcript levels in the flowering pathways determine flower bud formation and bud breaking. Generally, an increased VcFT/VcSOC1 ratio or increased VcSOC1 in leaf promotes precocious flowering and flower bud formation, and a decreased VcFT/VcSOC1 ratio with increased VcSOC1 in fully chilled flower buds contributes to flower bud breaking.